Silang Kuasa dalam Pengelolaan Zakat Era Kolonial Belanda - M. Nasrudin (Istitut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2015)
This paper describes power relations in almsgiving managerial at Dutch Colonial era with reviewing related works. Referring to the historical record, Dutch Colonial was not want to manage almsgiving practices from the first time coming. Colonial was not want to be judged as disturber to Islam, besides they have not knowledge regarding Islam. But after Snouck Hurgronje’s coming, one basic policy was decided regarding almsgiving. As obedience practices, almsgiving was allowed with restrictions, but as political practices almsgiving was not allowed. Dutch Colonial has an ambivalent view in order to almsgiving. Colonial was not want to be judged as disturber, but in another hand, Colonial has inducted penghulu (legal clerics), who was manage almsgiving and mosque finance. Penghulu was a government official, but their salary was not taken from State Budget but mosque budget. This almsgiving management was confusing and tends to mismanagement. So public tends to pay their almsgiving to tarbiyah (education) and dakwah (mission) clerics